Speech Acts in E-Commerce Customer Service: A Library Research on Pragmatic Strategies in Digital Communication - Fitriani, Eka Surya; Rosida, Sisi; Fadlan, Ahmad; Sylvana, Lestari (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This study investigates the use of speech acts in customer service conversations on Shopee, focusing on problem resolution and consumer complaints. Through a library research approach, the study examines existing literature on pragmatics and speech act theory, analyzing how directives, commissives, and expressives are used in managing customer service interactions in ecommerce platform such as Shopee, Lazada and Tokopedia. By reviewing relevant studies on speech acts in digital communication and customer service contexts, this research identifies common patterns and strategies employed by customer service representatives to address complaints and ensure customer satisfaction. The findings provide theoretical insights into the role of speech acts type such as expressive, directive and representative in e-commerce communication, contributing to a deeper understanding of effective customer service practices in shopping online platforms.